RESEARCH OF THE STABILITY OF SCOPE BOARDS OF QUARRY BOARDS USING THE ENGINEERING METHOD - Sherali Raufovich , Urinov; Agzam Muratovich , Askarov; Sevara Abdukarim kizi , Mansurova; Kahramon Abdukhailovich , Akhmedov; Muzaffar Bakhtiyorovich , Mirzakhmedov (Antis Publisher, 2024)
An engineering method for calculating the stability of slopes in quarries is considered, the slope angles of high ledges and the height of sub-ledges are established when forming a concave slope profile of a high ledge.